Correlation between indoor air pollution and adult respiratory health in Zunyi City in Southwest China: situation in two different seasons - Shixu Li; Jie Xu; Zhigang Jiang; Ya Luo; Yu Yang; Jie Yu (BMC, 2019)
Abstract Background Indoor environmental quality significantly influences the occurrence of asthma attack. Zunyi District has abundant coal reserves and is regarded as one of the cities that are most severely polluted by high levels of particulate matter in China. This study aimed to examine the correlation of indoor exposure with adult respiratory health, as well as the differences in effect between winter and summer. Methods A cross-sectional epidemiological study was conducted among 1207 adult residents in Zunyi, Guizhou Province of Southwest China in winter and summer. Data on health variables related to asthma and home environmental factors were collected using a modified European Community Respiratory Health Survey II questionnaire. The following data were obtained: samples of particulate matter 2.5 (PM2.5) inside and outside the households under study (n = 20); lung function status, including peak expiratory flow rate, forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and FEV1/FVC ratio. Result The odds ratio (OR) for asthma-like symptoms and asthma in adults using coal stove for cooking or warming, relative to non-users, was 1.73 (95% CI, 1.11-2.69) in winter vs. 1.30 (95% CI, 0.79-2.14) in summer. Adult residents with exposure to cooking oil fumes were at a considerably higher risk of asthma-like symptoms and asthma [OR = 2.65 (95% CI, 1.25 to 5.61) in winter vs. OR = 7.93 (95% CI, 2.54 to 24.75] in summer] than those without such exposure. The prevalence of asthma-like symptoms and asthma was significantly higher in adults with high kitchen risk scores or high sleeping-area risk scores than in those with low scores in both seasons (p < 0.05). The relative kitchen and sleeping area PM2.5 concentrations were higher in winter than in summer (p < 0.05). Lung function was negatively associated with indoor kitchen and sleeping area relative PM2.5 concentration in winter rather than summer (p < 0.001). The effect of exposure to indoor risk factors on lung function among the residents was greater in winter than in summer (p < 0.001). Conclusion Exposure to indoor risk factors, such as aerocontaminants from coal combustion, causes asthma symptoms and reduces pulmonary function. The effect of indoor risk factors on respiratory health among adults with such exposure was greater in winter than in summer.